Mejoras en el proceso de atención al cliente de créditos PYMES y el nivel de colocaciones de créditos en la Agencia La Esperanza - Trujillo EDPYME RAIZ en el periodo Enero - Octubre 2013. - Miranda Boado, Walter Jonathan (2014)
The present research is descriptive and has the problem How improvements in process customer credit increases the level of SME Credit loans on agency Esperanza Trujillo EDPYME ROOT in the period January-October 2013?, for which aims to determine how the process improvements in customer manage to increase the level of SME loan placements. As theoretical to illustrate the nature, characteristics and advantages of giving a good customer and involving all members of the business considerations are presented. They hypothesised having improvements in customer process allow favorably increase the level of SME credit loans. The methodology is based on fieldwork, which allowed collecting information of interest using direct collection strategies in reality under study. The techniques and instruments used were: questionnaire for institutional clients and another for staff, for which purpose it was considered as a sample to 269 customers and 11 employees. Analysis of the results led to the conclusion that root Edpyme improvements in customer process are favorable as is being achieved thanks to increased interest loans with customers by the company, because of the good care provided staff who treat them with kindness, effectively resolve the doubts and queries that clients may have, establishing a climate of trust and respect. It is therefore recommended always provide good service to every customer, without prejudice to any customer, for small customers, everyone should be treated equally no.